Mobile health technologies for the management of systemic lupus erythematosus: a systematic review. (February 2020) - Dantas, L O; Weber, S; Osani, M C; Bannuru, R R; McAlindon, T E; Kasturi, S
Objective: We aimed to perform a standardized review of available mobile health (mHealth) applications (apps) for systemic lupus erythematosus (SLE) and to conduct a systematic review of the literature on mHealth technologies in SLE. Methods: Google Play and AppStore in the United States of America were queried and the quality of eligible mHealth apps was assessed using the Mobile App Rating Scale (MARS). Web of Science, EMBASE, Medline, and Cochrane databases were systematically searched from inception through June 2019. Results: Of 324 mHealth apps found, 20 were eligible for inclusion; 10 focused on education, 7 offered tools to track patient-reported symptoms, 5 included interactive online communities, and 1 enabled emoji sharing. The reviewed apps scored poorly on the MARS quality scale with a mean score 2.3 (0.6) out of 5. Of 1147 studies identified in the literature review, 21 were eligible for inclusion; 11 studies (52.4%) focused on the development and use of mHealth for providing patient information, while only 2 (9.5%) were randomized trials of mHealth interventions. Conclusions: Although there is growing interest in the development of mHealth technologies to support SLE patients, currently available tools are of poor quality and limited functionality, and the literature examining this area is sparse.